2019
DOI: 10.1002/ece3.5097
|View full text |Cite
|
Sign up to set email alerts
|

American marten and fisher do not segregate in space and time during winter in a mixed‐forest system

Abstract: Understanding the mechanisms of coexistence between ecologically similar species is an important issue in ecology. Carnivore coexistence may be facilitated by spatial segregation, temporal avoidance, and differential habitat selection. American martens Martes americana and fishers Pekania pennanti are medium‐sized mustelids that occur sympatrically across portions of North America, yet mechanisms of coexistence between the two species are not fully understood. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 72 publications
4
16
0
Order By: Relevance
“…Because fishers only displaced martens in 1 per 291 marten visits, this suggests that martens had minimal loss of foraging opportunity due to short-term avoidance of fishers. Similar to a nearby study by Croose et al 25 , we found no evidence that martens altered their diel activity to avoid fishers; however, there was some temporal niche partitioning apparent where martens were more active than fishers during daylight. Finally, spatial overlap among fishers and martens was high, demonstrated by high (> 75%) co-occupancy of the same carcass sites and most observations of both species occurring at carcass sites previously visited by the other species.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Because fishers only displaced martens in 1 per 291 marten visits, this suggests that martens had minimal loss of foraging opportunity due to short-term avoidance of fishers. Similar to a nearby study by Croose et al 25 , we found no evidence that martens altered their diel activity to avoid fishers; however, there was some temporal niche partitioning apparent where martens were more active than fishers during daylight. Finally, spatial overlap among fishers and martens was high, demonstrated by high (> 75%) co-occupancy of the same carcass sites and most observations of both species occurring at carcass sites previously visited by the other species.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, sympatric martens and fishers may avoid each other by using different habitats 15 , 33 or by martens temporally avoiding fishers 21 . Where martens and fishers exhibit high spatio-temporal overlap, martens may be limited by fisher competition 16 or coexist with fishers with little apparent response as we observed in this study 25 . Our results suggest marten vigilance as a possible mechanism for coexistence with fishers despite high niche overlap.…”
Section: Discussionmentioning
confidence: 59%
“…Results of these two studies run counter to predictions based on range limit theory, where one would expect stronger biotic interactions at the southern range margin, but confirm likely issues caused by differences in scale. The scale of the study area used by Croose et al (2019) is likely to have constrained their ability to detect environmental heterogeneity and elucidate mechanisms that permit sympatry within a larger landscape, whereas the study of Fisher et al (2013) was conducted at a scale that incorporated substantial heterogeneity induced by gradients in topography and habitat.…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian predators and competitors may however play a major role in structuring the spatiotemporal behavior of this important prey species. Spatial niche partitioning and temporal segregation may allow coexistence between mesocarnivore and medium-sized species [ 3 , 15 , 19 , 21 , 23 ], particularly for those species showing high dietary overlap [ 19 , 21 ]. Despite being reported as a species also occasionally killed by free-ranging domestic cats, even in our study area [ 70 ], a low spatiotemporal overlap was observed between these species and the brown hare.…”
Section: Discussionmentioning
confidence: 99%
“…In the last ten years, many studies dealing with the activity rhythms of mammalian species and their interspecific overlap have been published [ 12 , 13 , 14 , 15 , 16 ]. These studies have mostly focused on prey-predator relationships involving large carnivores [ 16 , 17 , 18 ], intraguild interactions [ 19 , 20 , 21 , 22 , 23 ], population density and structure [ 24 ], and activity bouts at artificial feeding sites [ 25 , 26 ]. Conversely, little research has investigated spatiotemporal interactions amongst mesocarnivores and small-sized mammals, and between them and their potential predators [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%